Early Childhood Trauma Impact on Adolescent Brain Development, Decision Making Abilities, and Delinquent Behaviors: Policy Implications for Juveniles Tried in Adult Court Systems. (5th March 2020) - Williams, Ashley
Abstract: By examining previous literature on the brain's developmental process during adolescence, this paper aims to determine how early childhood trauma potentially effects decision making in adolescence through exploring self‐regulation theory. Through a self‐regulation framework, the hope is to determine the connection, if any, between early childhood trauma, delinquent behavior, and involvement in the juvenile justice system. The author insists that not only do adolescents have less culpability due to their brain developmental stage compared to adults, but also early childhood trauma puts adolescents at a greater risk of impaired self‐regulation which allows for more probable delinquent behavior. This paper also considers implications for social policy makers and youth advocates concerned with juvenile offenders tried in adult courts and existing racial disparities in the system.